Induction of Cross-Reactive Hemagglutination Inhibiting Antibody and Polyfunctional CD4+ T-Cell Responses by a Recombinant Matrix-M–Adjuvanted Hemagglutinin Nanoparticle Influenza Vaccine. (4th November 2020) - Shinde, Vivek; Cai, Rongman; Plested, Joyce; Cho, Iksung; Fiske, Jamie; Pham, Xuan; Zhu, Mingzhu; Cloney-Clark, Shane; Wang, Nan; Zhou, Haixia; Zhou, Bin; Patel, Nita; et al.
Abstract: Background: Recurrent reports of suboptimal influenza vaccine effectiveness have renewed calls to develop improved, broadly cross-protective influenza vaccines. Here, we evaluated the safety and immunogenicity of a novel, saponin (Matrix-M)–adjuvanted, recombinant hemagglutinin (HA) quadrivalent nanoparticle influenza vaccine (qNIV). Methods: We conducted a randomized, observer-blind, comparator-controlled (trivalent high-dose inactivated influenza vaccine [IIV3-HD] or quadrivalent recombinant influenza vaccine [RIV4]), safety and immunogenicity trial of qNIV (5 doses/formulations) in healthy adults ≥65 years. Vaccine immunogenicity was measured by hemagglutination-inhibition assays using reagents that express wild-type hemagglutination inhibition (wt-HAI) sequences and cell-mediated immune responses. Results: A total of 1375 participants were randomized, immunized, and followed for safety and immunogenicity. Matrix-M–adjuvanted qNIV induced superior wt-HAI antibody responses against 5 of 6 homologous or drifted strains compared with unadjuvanted qNIV. Adjuvanted qNIV induced post-vaccination wt-HAI antibody responses at day 28 that were statistically higher than IIV3-HD against a panel of homologous or drifted A/H3N2 strains, similar to IIV3-HD against homologous A/H1N1 and B (Victoria) strains and similar to RIV4 against all homologous and drifted strains evaluated. The qNIV formulation with 75 µg Matrix-M adjuvant induced substantially higher post-vaccination geometric mean fold increases of influenza HA-specific polyfunctional CD4+ T cells compared with IIV3-HD or RIV4. Overall, similar frequencies of solicited and unsolicited adverse events were reported in all treatment groups. Conclusions: qNIV with 75 µg Matrix-M adjuvant was well tolerated and induced robust antibody and cellular responses, notably against both homologous and drifted A/H3N2 viruses. Further investigation in a pivotal phase 3 trial is underway. Clinical Trials Registration: NCT03658629. Abstract : We compared multiple formulations of a recombinant Matrix-M–adjuvanted nanoparticle influenza vaccine with 2 licensed vaccines in older adults. The nanoparticle vaccine was well tolerated and induced hemagglutination-inhibition antibody and CD4+ T-cell responses to vaccine-homologous and drifted A/H3N2 influenza viruses.